Molecular data confirm the presence of Nycticebus bengalensis on Langkawi Island, Malaysia - BADRUL MUNIR MD ZAIN; KHAIRUL SYA’ADAH MOHHOYUA; NOR RAHMAN AIFAT; EHWAN NGADI; NORSHAQINAH AYOB; JEFFRINE JAPNING ROVIE-RYAN; AHMAD AMPENG; ABD RAHMAN MOHD-RIDWAN; MARY E BLAIR; MUHAMMAD ABU BAKAR ABDUL-LATIFF (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Md-Zain BM, Mohhoyua KS, Aifat NR, Ngadi E, Ayob N, Rovie-Ryan JJ, Ampeng A, Mohd-Ridwan AR, Blair ME, Abdul-Latiff MAB. 2019. Molecular data confirm the presence of Nycticebus bengalensis on Langkawi Island, Malaysia. Biodiversitas 20: 1115-1120. Recent taxonomic reviews have stated the possibility of Bengal Slow Loris (Nycticebus bengalensis) presence in the Northern part of the Malay Peninsula. This study aims to confirm the presence of the Bengal Slow Loris in Malaysia by sequencing the mitochondrial COI gene from samples collected from Langkawi Island, Peninsular Malaysia, and Borneo. Phylogenetic analyses produced tree topologies that support the grouping of slow loris samples by their localities. The tree topologies further show that slow loris samples from Sarawak and Peninsular Malaysia form two distinct clades. The clade from Peninsular Malaysia was divided into two subclades, Langkawi and Selangor. The Langkawi slow loris subclade includes sequences from GenBank representing N. bengalensis, supported by a high bootstrap value. This mitochondrial DNA finding has a significant contribution to indicate the presence of the Bengal Slow Loris in Malaysia.